Investigating traffic accidents: the interaction between a motor vehicle and a pedestrian - Sokolovskij, Edgar; Prentkovskis, Olegas (Transport, 2013)
The paper presents the methodology for expert investigation of traffic accidents involving running over pedestrians. This methodology is aimed at determining the availability of any technical possibility for a motor vehicle driver, driving at a particular speed, to avoid hitting the pedestrian in a particular situation. Furthermore, the paper presents the analysis of different investigation methods and the description of investigation procedures. Various patterns of the path of the motor vehicle and the pedestrian travel before the accident are described, providing a deeper insight into the peculiarities of investigation of each particular pattern. The description is supported by the case study, illustrating the investigation of a specific traffic accident, involving actual hitting of a pedestrian. The methodology presented may be successfully used for investigating traffic accidents by experts. First Published Online: 11 Oct 2013